2008
DOI: 10.1001/archneurol.2007.57
|View full text |Cite
|
Sign up to set email alerts
|

Plasma β Amyloid and the Risk of Alzheimer Disease and Dementia in Elderly Men

Abstract: Background: ␤ Amyloid (A␤) protein accumulates in the brains of individuals with Alzheimer disease (AD) and is detectable in cerebrospinal fluid and plasma.Objective: To examine plasma levels of A␤ peptides A␤ 40 and A␤ 42 as predictors of incident AD and other types of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 41 publications
3
71
2
1
Order By: Relevance
“…[47][48][49] Conversely, low baseline levels of plasma Ab1-40 at age 77 were associated with increased AD risk in men. 50 A lower plasma Ab1-42/Ab1-40 ratio was associated with increased risk for AD over a 3-year follow-up in a longitudinal study of 563 individuals. 51 In the largest longitudinal study to date, the combination of higher baseline Ab1-40 levels and lower Ab1-42 levels was associated with increased risk for dementia over a period of 8-9 years.…”
Section: Plasma Ab As a Diagnostic Markermentioning
confidence: 91%
“…[47][48][49] Conversely, low baseline levels of plasma Ab1-40 at age 77 were associated with increased AD risk in men. 50 A lower plasma Ab1-42/Ab1-40 ratio was associated with increased risk for AD over a 3-year follow-up in a longitudinal study of 563 individuals. 51 In the largest longitudinal study to date, the combination of higher baseline Ab1-40 levels and lower Ab1-42 levels was associated with increased risk for dementia over a period of 8-9 years.…”
Section: Plasma Ab As a Diagnostic Markermentioning
confidence: 91%
“…Similarly, other studies showed that elevated levels of Aβ-42 (van Oijen et al, 2006) low levels of Aβ-40 (Sundelof et al, 2008) or a reduced Aβ-42/Aβ-40 ratio in plasma (Graff-Radford et al, 2007) in aging could indicate the conversion from a normal cognitive status to MCI or AD. In contrast, others reported that reduced Aβ-42 plasma levels might reflect the evolution from normal aging or MCI to AD (Song et al, 2007), rather than a marker for neuropathological events occurring in the disease.…”
Section: Biomarkers In Plasmamentioning
confidence: 80%
“…Increased Ab or Ab 1-42 levels have been shown to predict the development of AD [113,114]; however, other analyses have revealed no associations [115,116] or opposite [117] results. A low Ab 1-42 /Ab 1-40 ratio is assumed to predict future AD [113,118,119].…”
Section: Blood Prospective Candidate Biomarkersmentioning
confidence: 97%